A Rare Case of Clear Cell Carcinoma, Müllerian Type in the Renal Pelvis of a 21-Year-Old Woman - Diandra Perez; Rana Naous (Case Reports in Pathology)
Clear Cell Carcinomas of Müllerian origin are extremely rare within the upper urinary system. Their morphology is identical to that of the Clear Cell Carcinomas of the female genital tract. When they arise in the urinary tract, it is thought to be due to ectopic Müllerian embryogenesis. Here, we present a case of a 21-year-old woman with a Clear Cell Carcinoma, Müllerian type, arising from the renal pelvis. Histologically, it consisted of tubulopapillary architecture with associated foamy macrophages and a mucinous background. The neoplastic cells exhibited variably sized round nuclei with prominent nucleoli, eosinophilic to vacuolated cytoplasm with occasional intracytoplasmic mucin vacuoles, and a hobnail appearance. Immunohistochemical stains showed that the neoplastic cells were positive for Pax-8, p53, CK7, HMWK 903, and INI-1 and focally positive for p504s (AMACR). The neoplastic cells were negative for GATA-3, CK5/CK6, p63, CK20, and CDX-2 immunostains, ruling out urothelial or enteric phenotype. Additional immunostains performed by an outside institution showed that the neoplastic cells were positive for HNF-1β. The overall morphology and immunophenotype were consistent with Clear Cell Carcinoma of Müllerian origin arising from the renal pelvis. Follow-up revealed no metastasis or other tumor sites, supporting that this was the primary location.